2013
DOI: 10.5187/jast.2013.55.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary β-Mannanase Supplementation and Palm Kernel Meal Inclusion on Laying Performance and Egg Quality in 73 Weeks Old Hens

Abstract: This study was conducted to evaluate the effect of dietary β-mannanase supplementation and palm kernel meal (PKM) inclusion (5%) on laying performance, egg quality and nutrient utilizability of laying hens with 73 weeks of age. A total of 240 Lohmann brown laying hens with average 77.5% egg production were randomly allocated with 60 hens per treatment, 4 replicates per treatment and 15 hens per replicate. Experimental design was a completely randomized design with 2 × 2 factorial arrangement, with the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
2
5
0
2
Order By: Relevance
“…In the present study, we initially analyzed the mannan contents of all feed ingredients and diets with low or high dietary mannan level were formulated to investigate the effects of the mannan level of diets and β -mannanase supplementation on egg production performance, nutrient retention, and blood metabolites in laying hens. The improved egg production performance of laying hens fed diets supplemented with β -mannanase was observed in the present experiment, which is in agreement with the data reported by Lee et al (2013) , who observed the improved egg production performance of laying hens fed maize-soybean or palm kernel meal-based diets that were supplemented with β -mannanase. Similarly, it was reported that dietary supplementation with β -mannanase improved egg production and growth performance in layers and broilers ( Wu et al , 2005 ; Zangiabadi and Torki, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we initially analyzed the mannan contents of all feed ingredients and diets with low or high dietary mannan level were formulated to investigate the effects of the mannan level of diets and β -mannanase supplementation on egg production performance, nutrient retention, and blood metabolites in laying hens. The improved egg production performance of laying hens fed diets supplemented with β -mannanase was observed in the present experiment, which is in agreement with the data reported by Lee et al (2013) , who observed the improved egg production performance of laying hens fed maize-soybean or palm kernel meal-based diets that were supplemented with β -mannanase. Similarly, it was reported that dietary supplementation with β -mannanase improved egg production and growth performance in layers and broilers ( Wu et al , 2005 ; Zangiabadi and Torki, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“… Ray et al (1982) and Daskiran et al (2004) reported that mannan significantly reduced growth and increased feed conversion ratio in broiler chickens. Previous studies have reported that supplementation of laying hen diets with β -mannanase could improve the egg production performance and nutrient utilization of laying hens ( Wu et al , 2005 ; Zangiabadi and Torki, 2010 ; Lee et al , 2013 ). Among the different types of β -mannanase available, bacterial β -mannanase appears to be the best option due to its high production rate, ease of control, and overall lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut penelitian Adrizal et al (2011), pemberian bungkil inti sawit sampai 30% dengan enzim pendegradasi serat pada ayam petelur umur 48 minggu tidak memperburuk produksi telur sedangkan, penambahan ß-Mannanase pada bungkil inti sawit 5% dapat meningkatkan produksi telur (Lee et al, 2013). Beberapa peneliti telah menemukan dampak positif degradasi enzimatik ß-Mannanase pada unggas.…”
Section: Pendahuluanunclassified
“…Berat telur dan HDP yang tidak signifikan dapat disebabkan karena jumlah kebutuhan nutrisi yang sudah mencukupi (Kim et al, 2017) dan tidak berkurang sekalipun ada penambaahan bungkil inti sawit hinggga 14% yang mengandung mannan. Parameter HDP dan berat telur senantiasa berbanding lurus dengan FI sebagaimana penelitian penggunaan bungkil inti sawit dan ß-Mannanase pada kualitas telur ayam petelur (Lee et al, 2013).…”
Section: Hasil Dan Pembahasanunclassified
“…Such poor nutrient utilization of PKM diets could be attributed to nonstarch polysaccharides (NSP) which are poorly utilized in poultry digestive system (Meng et al, 2005) and even act as anti-nutritive factors (Marquardt, 1997). Apparently supplementation of Hemicell ® in diet can break down β-mannan to mannooligosaccharides and simple sugar, and thus supply more nutrients for laying hens (Ferket et al, 2002;Hooge, 2004;Lee et al, 2013). Further, such supplementation increased feed intake and egg production in hens aged over 73 weeks.…”
Section: Effects Of Treatments On Egg Productionmentioning
confidence: 99%